Effects of storage temperature on shelf-life of mango coated with zinc oxide nanoparticles / Nur Syazwani Abdul Malek ... [et al.] - Abdul Malek, Nur Syazwani; Rosman, Nurfarhana; Mahmood, Mohamad Rusop; Khusaimi, Zuraida; Asli, Noor Asnida (Faculty of Applied Sciences, 2020)
Effect of different storage temperatures on physical and physiological changes of Golden Lily mango was investigated. Zinc oxide (ZnO) nanoparticles edible coating was prepared by sol-gel method and Golden Lily mangoes were dipped in the solution and stored at different (32 ℃, 27 ℃ and 5 ℃) temperatures for 7 days. The mangoes were characterized by Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-ray Spectroscopy (EDX), Fourier-transform Infrared Spectroscopy (FTIR) and X-ray Diffraction (XRD) after 7 days of storage. Both the analysis of FESEM and EDX revealed the highest volume ratio of ZnO nanoparticles with a homogeneous dispersion throughout the mango peel surface is at 5 ℃. FTIR spectra revealed the absence of Zn-O bonding as metal oxides absorption is expected to be in the region below 700 cm-1 . The mangoes stored at 5 ℃ delayed ripening, slowed down weight loss and found to be firmer than mangoes stored at 32 ℃ and 27 ℃.